Nurturing Creativity in the Visual Arts Classroom Understanding Teacher Strategies through Amabile's Componential Theory - Kukkonen, Tiina; Bolden, Benjamin (Canadian Review of Art Education / Revue canadienne d'éducation artistique)

(untitled) (Canadian Society for Education through Art, 2022)
Creative skill-building is a major focus of educational systems around the world. In this article, we draw on data from four K-12 visual arts teachers to illustrate pedagogical strategies used to support students’ creative development. We adopt Teresa Amabile’s Componential Theory of Creativity to frame the teachers’ approaches to creative skill-building, identifying how they nurtured students’task motivation, domain-specific skills, and creativity-relevant processes. By presenting the teaching strategies in this way, we hope to enable art educators to recognize, shape, and enhance how their own teaching can support the development of student creativity in the visual arts classroom.